PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMP NEGERI 3 SUNGGAL - Fitry Wahyuni (Universitas Islam Sumatera Utara, 2017)
Abstract. The aims of this research is to 1) the effectiveness of the learning process by using learning tools problem based learning learning model, include: (a) the achievement of student learning objectives views of problem solving skills both individually and classical, (b) active activity levels of students during the learning process, (c) the level of the teacher's ability to manage learning process, (d) student response of the components and the learning process; 2) increase students' problem solving skills using learning tools developed. Subjects in this study were students of class VII SMP Negeri 3 Sunggal as many as 34 people and the object of this study is to look at the effectiveness of the learning process is carried out. The instrument used consisted of observations of student activity sheets, a teacher's ability observation sheet, questionnaire responses of students and problem solving ability test. Learning tools developed (RPP, teacher books, student books, and activity sheets) already meets the level of validity with reliability coefficient is 0.788. Based on data obtained from tests on learning devices in mind that: 1) the device has been developed to meet the effectiveness of the learning process, wherein: (a) the percentage of students who reach the level of problem solving ability in classical 85,29% of the 34 students taking the test with a minimum value of 2,67 (B-), (b) the activity levels of students have met the tolerance limit LAS ideal time to good use in teaching in the first trial and the second trials, (c) the ability of teachers on the first trial is 2.90 and the second trials is 4,22, (d) student response to the components and the learning process has been positive on the first trial and second trials; 2) an increase in students' problem-solving ability of students at postest first trial, which increased 2,72 to 2,84 in postes second trial with an average increase in the medium category (average N-gain = 0.574).Keywords: learning tools, Problem Based Learning model, and problem solving Abstrak. Tujuan dari penelitian ini adalah untuk 1) keefektifan proses pembelajaran dengan menggunakan model pembelajaran berdasarkan masalah, meliputi: (a) pencapaian tujuan belajar siswa dilihat dari kemampuan pemecahan masalah baik secara individu maupun klasikal, (b) tingkat aktivitas aktif siswa selama proses pembelajaran, (c) tingkat kemampuan guru dalam mengelola proses pembelajaran, (d) respon siswa terhadap komponen dan proses pembelajaran; 2) meningkatkan kemampuan pemecahan masalah siswa dengan menggunakan perangkat pembelajaran yang dikembangkan. Subjek dalam penelitian ini adalah siswa kelas VII SMP Negeri 3 Sunggal sebanyak 34 orang dan objek penelitian ini adalah untuk melihat keefektifan proses pembelajaran yang dilakukan. Instrumen yang digunakan terdiri dari observasi lembar aktivitas siswa, lembar observasi kemampuan guru, kuesioner tanggapan siswa dan uji kemampuan pemecahan masalah. Alat pembelajaran yang dikembangkan (RPP, buku guru, buku pelajar, dan lembar kegiatan) sudah memenuhi tingkat validitas dengan koefisien reliabilitas sebesar 0,788. Berdasarkan data yang diperoleh dari pengujian perangkatpembelajaran diketahui bahwa: 1) perangkat telah dikembangkan untuk memenuhi keefektifan proses pembelajaran, dimana: (a) persentase siswa yang mencapai tingkat kemampuan pemecahan masalah pada kelas klasik 85, 29% dari 34 siswa yang mengikuti tes dengan nilai minimal 2,67 (B-), (b) tingkat aktivitas siswa telah memenuhi batas toleransi waktu ideal LAS untuk digunakan dengan baik dalam pengajaran di sidang pertama dan yang kedua. Uji coba, (c) kemampuan guru pada percobaan pertama adalah 2,90 dan uji coba kedua adalah 4,22, (d) tanggapan siswa terhadap komponen dan proses pembelajaran telah positif pada percobaan pertama dan uji coba kedua; 2) peningkatan kemampuan memecahkan masalah siswa pada percobaan pertama postest, yang meningkat 2,72 menjadi 2,84 pada postes second trial dengan kenaikan rata-rata kategori medium (rata-rata N-gain = 0,574). Kata Kunci: perangkat pembelajaran, pembelajaran berdasarkan masalah, dan pemecahan masalah